SOSIALISASI PERHITUNGAN HPP PRODUK UMKM DI DESA BUMI JAYA KECAMATAN PELAIHARI - Suwarno, Try Edi; Laoli, Victorinus; Setianda, Rizky Aldi; Sinaga, Ananda Sabrida Tora Boru; Muthmainnah, Riyadatul (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2025)
This journal discusses an outreach initiative on the calculation of the Cost of Goods Sold (COGS) conducted for Micro, Small, and Medium Enterprises (MSMEs) in Bumi Jaya Village. MSMEs play a vital role in economic growth and job creation in Indonesia. However, many MSME owners face challenges in financial management, particularly in accurately calculating COGS. This outreach aimed to enhance financial literacy and provide a clear understanding of the components of COGS, including raw material costs, labor, and overhead expenses. The training methods included lectures, practical applications, and mentoring, all designed to ensure participant engagement. The activity took place on October 31, 2024, and was met with high enthusiasm from participants, who expressed readiness to apply the acquired knowledge to their businesses. This initiative is expected to assist participants in setting competitive product prices and improving the sustainability of their enterprises.